Teoria e metodologia na escrita da História do Brasil: Afonso de Taunay e a Academia Brasileira de Letras - Araujo, Karina Anhezini de [UNESP] (My University, 2010)
The history of historiography in recent decades has the breathing space needed in the concerns of historians and has been transformed into a research field with its own issues. Uploaded this in perspective, this paper aims to understand how aspects of the theory of history and methodology have been addressed by Afonso de Escragnolle Taunay (1876-1958). We selected the letters exchanged by the author, the speeches of acceptance at the ABL, some articles and books produced by Taunay in the 1930s. In the first decades of the twentieth century, when it sought to define the historiography and its limits in both the literature and social science sources, the subjectivity is presented as the final decision making of the author, especially those related to the new site production Taunay, the Brazilian Academy of Letters.

A história da historiografia conquistou nas últimas décadas um espaço necessário nas preocupações dos historiadores e tem se transformado em um campo de pesquisas com questões próprias. Inserido nessa perspectiva, esse artigo pretende compreender como aspectos da história da teoria e da metodologia foram abordados por Afonso de Escragnolle Taunay (1876-1958). Para tanto, foram selecionadas as correspondências trocadas pelo autor, os discursos de recep- ção na ABL, alguns artigos e livros produzidos por Taunay na década de 30. Nas primeiras décadas do século XX, quando se buscava a definição da historiografia e de seus limites tanto em relação à literatura quanto às ciências sociais nascentes, as subjetividades se apresentaram como definitivas nas tomadas de decisão do autor, especialmente, àquelas relacionadas ao novo local de produção de Taunay, a Academia Brasileira de Letras.
Keywords: Brazilian historiography; Academy of Letters; Afonso de Taunay; Historiografia brasileira; Academia Brasileira de Letras; Afonso de Taunay